2010
DOI: 10.1111/j.1574-6941.2010.00932.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of trace element addition on biogas production from food industrial waste - linking process to microbial communities

Abstract: Laboratory-scale reactors treating food industry waste were used to investigate the effects of additions of cobalt (Co), nickel/molybdenum/boron (Ni/Mo/B) and selenium/tungsten (Se/W) on the biogas process and the associated microbial community. The highest methane production (predicted value: 860 mL g(-1) VS) was linked to high Se/W concentrations in combination with a low level of Co. A combination of quantitative real-time PCR of 16S rRNA genes, terminal restriction fragment length polymorphism (T-RFLP) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
76
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 174 publications
(85 citation statements)
references
References 78 publications
8
76
1
Order By: Relevance
“…Trace metals are important micronutrients for growth and activity of microorganisms in biogas reactors in which organic content of the influent material is biologically converted to methane and carbon dioxide under anaerobic conditions [6][7][8][9][10]. Processes regulating the chemical speciation and bioavailability of trace metals are complex involving dynamic interaction of microorganisms with organic and inorganic compounds [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Trace metals are important micronutrients for growth and activity of microorganisms in biogas reactors in which organic content of the influent material is biologically converted to methane and carbon dioxide under anaerobic conditions [6][7][8][9][10]. Processes regulating the chemical speciation and bioavailability of trace metals are complex involving dynamic interaction of microorganisms with organic and inorganic compounds [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Increases in VFA corresponded to an increasing total ammonia nitrogen concentration which appeared to become inhibitory at ~2500 mg N l -1 . It has been shown that in mesophilic conditions accumulation of VFA can be prevented by supplementing with selected trace elements [17][18][19][20]. Mesophilic food waste digesters supplemented with trace elements have been shown to operate with good gas production and low VFA concentrations at ammonia concentrations in excess of 6000 mg l -1 , but with a purely hydrogenotrophic methanogenic population; and a mechanism by which trace element addition can prevent VFA accumulation at high ammonia concentrations has been put forward [18].…”
mentioning
confidence: 99%
“…These results showed that iron addition stimulated the methanation activity by enriching critical methanation functional microorganisms. Methanoculleus was reported as saline tolerance and correlated with TE supplementation (Feng et al 2010), which was stimulated by copper and mixed TE group. Methanoculleus was dominated in the recovery group of mixed TE supplementation in which methanation was completely inhibited.…”
Section: Methanogen Growthmentioning
confidence: 98%